Sustainability reporting in airlines industry: evidence from Turkey - Selimoglu, Seval Kardes; Caliskan, Arzu Ozsozgun (INDERSCIENCE ENTERPRISES LTD, 2018)
Airlines are a crucial driver for economic and social development, connecting people, delivering products and transporting goods. Today, there is a much clearer recognition of the need to consider aviation's contribution to the three pillars of sustainability; economic, social and environment in a more integrated manner Even sustainability reporting is popular subject in academic literature, sustainability reporting related researches are limited in the airlines. The main aim of this research paper is to address the status of sustainability reports in Turkish aviation industry by focusing airlines. In 2016, there are 13 airlines companies operating in Turkey's civil aviation industry in the field of passenger and cargo carriage. Data of the research collected through web sites visits of the companies, the GRI disclosure database, the public disclosure database (KAP) in Turkey. The results show that sustainability reporting practices are not common in Turkey's aviation industry. Among the 13 airlines companies, only one airlines company has sustainability reports. In addition to that, there is one airport operation company and one ground handling company in the sector that publish sustainability reports.
Keywords: sustainability; sustainability reporting; corporate reporting; aviation; airlines; developing country; emerging economy; Turkey; CORPORATE SOCIAL-RESPONSIBILITY; CSR; PERFORMANCE; INDICATORS; Engineering